The T160A hemagglutinin substitution affects not only receptor binding property but also transmissibility of H5N1 clade 2.3.4 avian influenza virus in guinea pigs. (January 2018) - Gu, Min; Li, Qunhui; Gao, Ruyi; He, Dongchang; Xu, Yunpeng; Xu, Haixu; Xu, Lijun; Wang, Xiaoquan; Hu, Jiao; Liu, Xiaowen; Hu, Shunlin; Peng, Daxin; et al.
Abstract We generated and characterized site-directed HA mutants on the genetic backbone of H5N1 clade 2.3.4 virus preferentially binding to α-2, 3 receptors in order to identify the key determinants in hemagglutinin rendering the dual affinity to both α-2, 3 (avian-type) and α-2, 6 (human-type) linked sialic acid receptors of the current clade 2.3.4.4 H5NX subtype avian influenza reassortants. The results show that the T160A substitution resulted in the loss of a glycosylation site at 158N and led not only to enhanced binding specificity for human-type receptors but also transmissibility among guinea pigs, which could be considered as an important molecular marker for assessing pandemic potential of H5 subtype avian influenza isolates.